Housing Instability and HIV Risk: Expanding our Understanding of the Impact of Eviction and Other Landlord-Related Forced Moves - Groves, Allison K. (AIDS Behav, 2021)
The study purpose is to comprehensively measure landlord-related forced moves (inclusive of, but not restricted to, legal eviction), and to examine whether landlord-related forced moves is associated with HIV risk. Baseline survey data was collected between 2017 and 2018 among 360 low-income participants in New Haven, Connecticut. We used multivariable logistic regression analyses to examine associations between landlord-related forced moves and HIV sexual risk outcomes. Seventy seven out of three hundred and sixty participants reported a landlord-related forced move in the past 2 years, of whom 19% reported formal eviction, 56% reported informal eviction and 25% reported both. Landlord-related forced moves were associated with higher odds of unprotected sex (AOR 1.98), concurrent sex (AOR 1.94), selling sex for money or drugs (AOR 3.28), exchange of sex for a place to live (AOR 3.29), and an HIV sexual risk composite (ARR 1.46) (p < .05 for all). We found robust associations between landlord-related forced moves and HIV sexual risk. Findings suggest that the social and economic consequences of landlord-related forced moves may impact sexual vulnerability.